1997
DOI: 10.1074/jbc.272.43.27178
|View full text |Cite
|
Sign up to set email alerts
|

SOCS-1/JAB/SSI-1 Can Bind to and Suppress Tec Protein-tyrosine Kinase

Abstract: Tec is the prototype of a recently emerging subfamily among nonreceptor type protein-tyrosine kinases and is known to become tyrosine-phosphorylated and activated by a wide range of cytokine stimulations in hematopoietic cells. Although Tec was recently shown to be involved in the cytokine-driven activation mechanism of c-fos transcription, it is yet obscure how Tec relays the signals from cell surface receptors to the nucleus. To identify signaling molecules acting downstream of Tec, we have looked for Tec-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(54 citation statements)
references
References 22 publications
1
53
0
Order By: Relevance
“…Some data suggest that SOCS-2 may interact directly with the insulin-like growth factor-1 receptor and possibly regulate its function (45). Furthermore, SOCS-1 has been shown to inhibit Tec tyrosine kinases (46). These results suggest that the inhibitory function of SOCS proteins may extend beyond that of JAKs and cytokine receptors.…”
Section: Socs-3 Inhibits Leptin-induced Tyrosine Phosphorylation Of Jmentioning
confidence: 84%
“…Some data suggest that SOCS-2 may interact directly with the insulin-like growth factor-1 receptor and possibly regulate its function (45). Furthermore, SOCS-1 has been shown to inhibit Tec tyrosine kinases (46). These results suggest that the inhibitory function of SOCS proteins may extend beyond that of JAKs and cytokine receptors.…”
Section: Socs-3 Inhibits Leptin-induced Tyrosine Phosphorylation Of Jmentioning
confidence: 84%
“…We have previously shown that the N-terminal sequences contain classical diproline motifs involved in the binding of SH3-containing molecules including ITK, p85 and GRB2 (De Sepulveda et al, 1999). The central SH2 domain is responsible for binding to both tyrosine phosphorylated proteins such as JAKs, KIT, and TEC and to the non-phosphorylated N-terminus of VAV Endo et al, 1997;Ohya et al, 1997). Lastly, the conserved C-terminal SOCS-Box binds to Elongin C (Kamura et al, 1998;Zhang et al, 1999).…”
Section: Inhibition By Socs-1 Is Not Dependent On the Kit/ Socs-1 Phymentioning
confidence: 99%
“…It can also associate with, and reduce the activity of, tyrosine kinases Tyk2 (Naka et al, 1997) and Tec, but not Lyn (Ohya et al, 1997). Interestingly, SOCS-1 has been shown to suppress stem cell factor (SCF)-induced proliferation, while favoring viability promoted by this cytokine (De Sepulveda et al, 1999).…”
Section: Introductionmentioning
confidence: 99%